Prevalence of asthma in Rhodesian Africans. Issue 11 (November 1980) - Cookson, J B; Makoni, G
Abstract : The prevalence of asthma in a small African town has been assessed using two questionnaires. The first was put to 9768 subjects aged 5 years and older and the second, more detailed, questionnaire to random selections of these subjects grouped according to their replies. The overall prevalence of asthma was 1.40%. In those under 20 years of age it was 1.20% and in adults, 1.57%. This adult rate is similar to those in developed countries but that in children is lower. The relative paucity of childhood asthma is compatible with the suggestion that infestation with parasites may protect against the disease.